UJI KEAMANAN KOMUNIKASI VOIP MENGGUNAKAN SISTEM KEAMANAN SRTP-TLS PADA JARINGAN NIRKABEL - Handayani, Tri Febriana; Sudiarta, Pande Ketut; Oka Widyantara, I Made (Jurnal SPEKTRUM; Vol 5 No 1 (2018): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2018.v05.i01.p02, 2018)
VoIP is a technology used to communicate voice remotely and directly using data communication lines with TCP / IP protocol. But basically, VoIP communication does not guarantee data security when doing communication. A very important security system is added in VoIP communications to maintain the confidentiality of communication, so that communication can not be recorded and played back. To build a security when communicating VoIP, then in this study added an SRTP-TLS security system. The study was conducted on wireless networks by comparing the security of data communications when using the SRTP-TLS security system and without using a security system. Keywords: Wireless, Security System, VoIP